Endothelium Independent Effect of Pelargonidin on Vasoconstriction in Rat Aorta - Min, Young Sil (Biomol Ther (Seoul), 2018)
In this study, we investigated the effects of pelargonidin, an anthocyanidin found in many fruits and vegetables, on endothelium-independent vascular contractility to determine the underlying mechanism of relaxation. Isometric contractions of denuded aortic muscles from male rats were recorded, and the data were combined with those obtained in western blot analysis. Pelargonidin significantly inhibited fluoride-, thromboxane A2-, and phorbol ester-induced vascular contractions, regardless of the presence or absence of endothelium, suggesting a direct effect of the compound on vascular smooth muscles via a different pathway. Pelargonidin significantly inhibited the fluoride-dependent increase in the level of myosin phosphatase target subunit 1 (MYPT1) phosphorylation at Thr-855 and the phorbol 12,13-dibutyrate-dependent increase in the level of extracellular signal-regulated kinase (ERK) 1/2 phosphorylation at Thr202/Tyr204, suggesting the inhibition of Rho-kinase and mitogen-activated protein kinase kinase (MEK) activities and subsequent phosphorylation of MYPT1 and ERK1/2. These results suggest that the relaxation effect of pelargonidin on agonist-dependent vascular contractions includes inhibition of Rho-kinase and MEK activities, independent of the endothelial function.